22.9k views
0 votes
Prove that tan² theta + cot² theta = sec² theta cosec² theta- 2​

User Sarra
by
4.8k points

2 Answers

5 votes

Please find attached herewith the solution of your question.

If you have any doubt, please comment.

Prove that tan² theta + cot² theta = sec² theta cosec² theta- 2​-example-1
User NielsK
by
4.3k points
3 votes

Explanation:

Tan² theta = sec² theta - 1

Cot² theta = cosec² theta - 1

Tan²+Cot² = sec²-1+cosec²-1

= sec²+cosec²-2

User Josh Cartwright
by
5.0k points